Configurable embedded solution for multi-mode motor control - Ufuk Guner (International Journal of Reconfigurable and Embedded Systems (IJRES), 2026)
Precise robotic systems often require multiple motor types, which increases hardware complexity, cost, and synchronization effort. This study presents an open-source multi-mode motor control platform based on four half-bridge power stages, enabling direct current (DC), brushless direct current (BLDC), and step per motor control on a single hardware architecture. Unlike existing software based multi-mode approaches, the proposed system introduces automatic motor type identification and safe connection verification at the hardware level, re quiring only a microcontroller and a integrated power stage. This represents a key novelty of the platform. Experimental validation was performed using three different motor types. The system achieved correct motor classification over re peated identification tests, with no false detections. Position control experiments confirmed stable operation across DC, BLDC, and stepper motor. The results demonstrate that the proposed platform significantly reduces system complexity while providing reliable multi-motor operation in a compact and low-cost structure.